One-Step Cutting of Multi-Walled Carbon Nanotubes Using Nanoscissors - Zhao, Jiang; Liu, Ping; Yang, Zhi; Zhou, Peng; Zhang, Yafei (Nano-Micro Letters, 2011)
A novel, simple and effective one-step method has been developed to cut the conventional long and entangled multi-walled carbon nanotubes (MWCNTs) with nanoscissors. The cutting process was carried out by the interactive collision of CNTs with the silicon carbide particles adhered on the abrasive papers. The final cut nanotubes have an average length of 200∼300 nm. The statistical length distribution result indicates that cutting by this method achieves high cutting efficiency for short duration of 2 min. Shortened nanotubes are found to be easily dispersed into aqueous and ethanol solutions. The cut MWCNTs/copper composite thin film fabricated by combined electrophoresis and electroplating techniques reveals that MWCNTs after cutting are well distributed and adhered to the Cu matrix. This method is not only fast and efficient but also no chemical waste, which will expand many potential applications of CNTs.